Correlation between surface properties and wettability of multi-scale structured biocompatible surfaces. Issue 1 (October 2015) - Gorodzha, S N; Surmeneva, M A; Prymak, O; Wittmar, A; Ulbricht, M; Epple, M; Teresov, A; Koval, N; Surmenev, R A
Abstract: The influence of surface properties of radio-frequency (RF) magnetron deposited hydroxyapatite (HA) and Si-containing HA coatings on wettability was studied. The composition and morphology of the coatings fabricated on titanium (Ti) were characterized using atomic force microscopy (AFM) and X-ray diffraction (XRD). The surface wettability was studied using contact angle analysis. Different geometric parameters of acid-etched (AE) and pulse electron beam (PEB)-treated Ti substrates and silicate content in the HA films resulted in the different morphology of the coatings at micro- and nano- length scales. Water contact angles for the HA coated Ti samples were evaluated as a combined effect of micro roughness of the substrate and nano-roughness of the HA films resulting in higher water contact angles compared with acid-etched (AE) or pulse electron beam (PEB) treated Ti substrates.